2014
DOI: 10.2190/pm.47.1.d
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem and Psychiatric Features of Turkish Adolescents with Psychogenic Non-Epileptic Seizures: A Comparative Study with Epilepsy and Healthy Control Groups

Abstract: It could be concluded that both disorders involved a high risk for developing psychiatric disorders; additionally, adolescents with PNES have higher rates of stressors and lower levels of self-esteem. Findings from this investigation point to the importance of psychiatric interventions in pediatric PNES and also epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 26 publications
1
24
0
1
Order By: Relevance
“…To the best of our knowledge, this is the first study reporting ADHD (61%) and disruptive behavior disorders (33%) as the most frequent psychiatric disorders in boys with PNES. Similarly, a previous study reported ADHD (29.4%) and depression (26.4%) as the two most common diagnoses in juvenile age PNES [19]. There is evidence for female predominance in depression and male predominance in ADHD in the general population [20,21].…”
Section: Psychopathologysupporting
confidence: 54%
“…To the best of our knowledge, this is the first study reporting ADHD (61%) and disruptive behavior disorders (33%) as the most frequent psychiatric disorders in boys with PNES. Similarly, a previous study reported ADHD (29.4%) and depression (26.4%) as the two most common diagnoses in juvenile age PNES [19]. There is evidence for female predominance in depression and male predominance in ADHD in the general population [20,21].…”
Section: Psychopathologysupporting
confidence: 54%
“…Thirty-one studies included adult subjects (mean age 37.1 yrs, range 18-77yrs) [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][44][45][46][48][49][50][51][52][54][55][56][57][58][59][60] , whereas the remaining three studies came from a paediatric setting (mean age 13.7 yrs, range 9-18 yrs) 43,47,53 . In both the cases and control samples, most subjects were female (79.7% cases vs 72.2% controls).…”
Section: Included Studiesmentioning
confidence: 99%
“…In both the cases and control samples, most subjects were female (79.7% cases vs 72.2% controls). In 25 out of 34 studies the patients were recruited from a neurology setting 27,[29][30][31][32]34,35,[37][38][39][40][41][43][44][45][46][47][48][49][50]52,55,57,58,60 , eight came from psychiatry 28,33,36,42,51,53,54,56 and one study came from a mixed setting 59 . Eighteen studies out of 34 compared the functional patient group with a neurological disease control group 27,29,30,32,34,35,[37][38][39][40][44][45][46]48,[50]…”
Section: Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations